Competition Among Regulators - Marquez, Robert; Dell'Ariccia, Giovanni (Washington, D.C. : International Monetary Fund, 2001)
This paper shows that competition among regulators reduces regulatory standards relative to a centralized solution. It suggests that a central regulator is more likely to emerge for homogeneous and financially integrated countries. The paper proves these results in a model where regulators concerned with their banking system's stability and efficiency and with their banks' profitability set their regulatory policy non-cooperatively. Externalities in bank regulation make the independent solution collectively inefficient. These externalities and the benefits of centralized regulation increase with financial integration, while the costs associated with the loss of independence decrease with the homogeneity of the countries involved.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet